2020
DOI: 10.1038/s41598-020-57628-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microbial inoculants on the fermentation characteristics and microbial communities of sweet sorghum bagasse silage

Abstract: Sweet sorghum bagasse (SSB) is a promising raw material for silage fermentation due to its high residual nutritive, but the efficient fermentation strategy of SSB has not been reported yet. This study evaluated the effects of microbial inoculant on the fermentation quality, chemical composition and microbial community of SSB silage. The silage inoculated with isolated lactic acid bacteria (LpE) achieved better fermentation than that of commercial inoculant A, B (CIA, CIB) and untreatment, including low pH valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 48 publications
14
20
0
1
Order By: Relevance
“…These genera were mainly observed in the CK group. These results were in accordance with former studies reported by Ogunade et al (2018) , Yang et al (2019) , and Dong et al (2020) . Hetero-fermentative LAB like Weissella are less efficient in decreasing pH than homofermentative Lactobacillus .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These genera were mainly observed in the CK group. These results were in accordance with former studies reported by Ogunade et al (2018) , Yang et al (2019) , and Dong et al (2020) . Hetero-fermentative LAB like Weissella are less efficient in decreasing pH than homofermentative Lactobacillus .…”
Section: Discussionsupporting
confidence: 94%
“…AQS accurately illustrated the dynamics in absolute abundance of bacterial community in alfalfa silage using synthetic chimeric DNA spikes, and uncovered more sequencing information analyzing alpha and beta diversities of bacterial communities than RQS. Dong et al (2020) reported a reduction in richness of bacterial community through the ensiling process in Broussonetia papyrifera and perennial ryegrass mixed silage. Similarly, bacterial richness indices in our study reduced at 60days compared with the 10-day alfalfa silage.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus plantarum (LP) and sucrose (S) are widely used to promote lactic acid fermentation and restrict clostridial fermentation, which improvs the silage quality of moist forage crops 15 , 16 . Most previous studies only reported how changes in the bacterial community affect the quality of silage 6 , 17 , 18 , whereas the effects of these additives on clostridial diversity are unclear. We previously analyzed the clostridial community dynamics of alfalfa silage following addition of both LP and S. However, the clostridial community dynamics were not detected when LP or S was added separately.…”
Section: Introductionmentioning
confidence: 99%
“…Both inoculants were effective in reducing the pH relative to the control silage. Sufficient concentrations of soluble carbohydrates are required as the fuel for lactic acid bacteria (Tomaz et al, 2018;Dong et al, 2020). When this condition is met, the bacteria present in the inoculants produce lactic acid and acetic acid, resulting in lowered pH (Holzer et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of these studies have been contradictory and inconclusive. It is believed that differences among the strains of bacteria that were used contributed to the disparate effects (Dong et al, 2020). Ávila et al (2009) described improvements in the fermentation profile and reduction of fungi concentration in Mombaça guinea grass silage that was inoculated with Lactobacillus buchneri.…”
Section: Introductionmentioning
confidence: 99%